Cross-modal metaphorical mapping of spoken emotion words onto vertical space - Montoro, Pedro R.; Contreras, María José; Elosúa, María Rosa; Marmolejo-Ramos, Fernando (Frontiers in Psychology, 2015)
From the field of embodied cognition, previous studies have reported evidence of metaphorical mapping of emotion concepts onto a vertical spatial axis. Most of the work on this topic has used visual words as the typical experimental stimuli. However, to our knowledge, no previous study has examined the association between affect and vertical space using a cross-modal procedure. The current research is a first step toward the study of the metaphorical mapping of emotions onto vertical space by means of an auditory to visual cross-modal paradigm. In the present study, we examined whether auditory words with an emotional valence can interact with the vertical visual space according to a ‘positive-up/negative-down’ embodied metaphor. The general method consisted in the presentation of a spoken word denoting a positive/negative emotion prior to the spatial localization of a visual target in an upper or lower position. In Experiment 1, the spoken words were passively heard by the participants and no reliable interaction between emotion concepts and bodily simulated space was found. In contrast, Experiment 2 required more active listening of the auditory stimuli. A metaphorical mapping of affect and space was evident but limited to the participants engaged in an emotion-focused task. Our results suggest that the association of affective valence and vertical space is not activated automatically during speech processing since an explicit semantic and/or emotional evaluation of the emotionally valenced stimuli was necessary to obtain an embodied effect. The results are discussed within the framework of the embodiment hypothesis.